Emission factors from residential combustion appliances burning Portuguese biomass fuels - Fernandes, A. P.; Alves, C. A.; Goncalves, C.; Tarelho, L.; Pio, C.; Schimdl, C.; Bauer, H. (Journal of Environmental Monitoring, 2011)
Smoke from residential wood burning has been identified as a major contributor to air pollution, motivating detailed emission measurements under controlled conditions. A series of experiments were performed to compare the emission levels from two types of wood-stoves to those of fireplaces. Eight types of biomass were burned in the laboratory: wood from seven species of trees grown in the Portuguese forest (Pinus pinaster, Eucalyptus globulus, Quercus suber, Acacia longifolia, Quercus faginea, Olea europaea and Quercus ilex rotundifolia) and briquettes produced from forest biomass waste. Average emission factors were in the ranges 27.5-99.2 g CO kg-1, 552-1660 g CO2 kg-1, 0.66-1.34 g NO kg-1, and 0.82-4.94 g hydrocarbons kg-1 of biomass burned (dry basis). Average particle emission factors varied between 1.12 and 20.06 g kg-1 biomass burned (dry basis), with higher burn rates producing significantly less particle mass per kg wood burned than the low burn rates. Particle mass emission factors from wood-stoves were lower than those from the fireplace. The average emission factors for organic and elemental carbon were in the intervals 0.24-10.1 and 0.18-0.68 g kg-1 biomass burned (dry basis), respectively. The elemental carbon content of particles emitted from the energy-efficient "chimney type" logwood stove was substantially higher than in the conventional cast iron stove and fireplace, whereas the opposite was observed for the organic carbon fraction. Pinus pinaster, the only softwood species among all, was the biofuel with the lowest emissions of particles, CO, NO and hydrocarbons.
The following values have no corresponding Zotero field: publisher: The Royal Society of Chemistry
Keywords: Biomass combustion; Emission factors; Wood stove (voyant)